Thin films composed of Au nanoparticles embedded in AlN: Influence of metal concentration and thermal annealing on the LSPR band - Domingues, R. P. (2018)
Nanocomposite thin films, with noble nanoparticles dispersed in a dielectric matrix, are known to present unique optical properties. Based on the Localized Surface Plasmon Resonance (LSPR) phenomenon, these "nanoplasmonic" materials are the basis of a wide range of technological applications, namely (bio)molecular LSPR-sensors. They are regulated by the concentration, size, shape and distribution of the nanoparticles and dielectric environment properties. In this work, the possibility of using aluminium nitride (AlN) as a host dielectric matrix for LSPR films was evaluated. For this purpose, nanocomposite Au:AlN films were prepared by magnetron sputtering, followed by thermal annealing to promote the growth of the nanoparticles. Three sets of films were deposited with atomic Au concentrations of 2.2, 4.4 and 6.0 at.%. LSPR bands appeared from the temperature of 500 degrees C, with resonance positions of 520-540 nm. The films showed potential to be tested in LSPR-sensing applications due to their optical responses.